Accelerating Students’ Speaking Skill Through Time Token Technique - Moetia, Meristika; Adani, Sukri (IJELR: International Journal of Education, Language, and Religion, 2024)
This study aimed at investigating the use of time token technique in improving students speaking skill. The researcher adopted experimental approach type pretest and posttest control group design to overcome the problem faced by students in learning speaking skill. An oral speaking test was designed to be used as research instrument in order to collect the data needed for this study. The researcher used speaking criteria that proposed by Brown (2004) to analyze the result of the test. Thus, some statistical formula (t-test) from Sudjana (2002) were also used to measure the improvement of students’ speaking skill in pretest and posttest for experimental and control class. The result revealed that t-score (8.7) > t-table (1.68), so there is an improvement of students’ speaking skill in experimental group after taught by using time token technique aided descriptive text. It means that time token technique is effective to be used in teaching process, and can be one of the alternative techniques used by teacher in teaching speaking for English as foreign language class